Removal of the Rhodamine B Dye at Ti/Ru0.3Ti0.7O2 Anode Using Flow Cell System - Ali Baddouh; Brahim El Ibrahimi; Elhassan Amaterz; M. Mohamed Rguiti; Lahcen Bazzi; Mustapha Hilali (Journal of Chemistry)
The electrochemical oxidation of the Rhodamine B dye (Rh-B) was carried out using dimensionally stable type anode (DSA, Ti/Ru0.3Ti0.7O2). The work was performed using the electrochemical flow cell system. The effect of several operating factors, such as supporting electrolytes, current density, electrolysis time, temperature, and initial concentration of Rh-B dye, were investigated. The UV-visible spectroscopy and chemical oxygen demand (COD) measurements were conducted to monitor the removal and degradation of Rh-B. The best color removal achieved was found to be 98.3% after 10 min applying 3.9 mA·cm−2 as a current density using 0.07 mol·L−1 of NaCl. Meanwhile, the highest COD removal rate (93.0%) was obtained for an applied current density of 3.9 mA·cm−2 as the optimal operating condition after 180 min reaction time, with 2.98 kW h·m−3 as energy consumption. This shows that the best conditions for color removal are not certainly the same as those for the COD removal. The rises in the concentration of NaCl, and applied current increased the Rh-B color removal rate. The decline in Rh-B dye concentration followed pseudo-first-order kinetics. The obtained values of apparent rate constant were increased by increasing chloride ion concentration. It is concluded that the electro-oxidation on DSA electrode using a flow cell is a suitable process for the removal of Rh-B dye in aqueous solutions.